Agir en compétence dans les centres d’appels : dilemmes entre emploi, travail et santé - Simone Santos Oliveira; Jussara Brito; Marianne Lacomblez (Perspectives Interdisciplinaires sur le Travail et la Santé)
This article aims to highlight how the ergological concept of “managerial dimension” of call center operators’ activity influences the relations between health and disease. The technique of instructions to a double, meetings with these social protagonists and the analysis of discourse obtained in this occasions haven’t highlighted how much the combination of contradictory injunctions, in a strongly normative framework that ignores the complexity of work, leads to a use of oneself whose consequences are detrimental to health, career and job preservation. Nevertheless, an "action competence" is evidenced, characterized by another use of prescriptions, pauses, script and voice. However, the precarious conditions in which the work is developed are hardly compatible with the construction of experience and collectives capable of facing the specific difficulties of this activity, as it is defined. The article concludes by returning to the point raised by the evoked research on the plan of union intervention. The article also emphasized the importance of international comparisons, which have the merit to remember that there are always options in deciding on the rules governing the work.